Indonesian democracy’s resilience: A case study of women's representation in Jakarta provincial legislature - Hanita, Margaretha; Dharmayudha, I Gede Ngurah Eka; Mulyadi, Mulyadi (International Journal Labs, 2024)
Women's representation in government is considered able to reflect the resilience of democracy in Indonesia. This study aims to analyze the resilience of democracy in DKI Jakarta by looking at the representation of women in the legislative ranks of the DKI Jakarta Provincial DPRD. The method in research is a qualitative approach with literature study methods and case studies on women's representation in the legislative ranks of the DKI Jakarta DPRD. The results showed that women's involvement in politics in the DKI Jakarta DPRD in 2009, 2014, and 2019 was still not in accordance with Article 65 paragraph (1) of Law Number 12 of 2003 concerning Elections where it was stated that election participants could submit candidates for members of the DPR, Provincial DPRD, and Regency / City DPRD for each electoral area by taking into account the representation of women at least 30 percent. In 2009, out of a total of 94 seats, only 22 seats (23.40%) were occupied by women, while the rest were by men. Then, in 2014, the number of female seats was slightly reduced to 19 seats (17.92%), while in 2019, there was an increase to 23 seats (21.70%). The mismatch of women's representation in political seats can cause concern about the resilience of Indonesia's democracy. When women's involvement in the political decision-making process is too low, there will be indications of imbalances in political representation and reducing the plurality of voices in the policy-making process.